Workshop, Assistance, and Capacity Building in the Development of Teaching Materials Based on 21st-Century Learning - Fuad Ahmad Rivai; Nisa Rahmawati (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
The community service program conducted at Pondok Modern Darussalam Bogor aimed to enhance teachers’ abilities in developing 21st-century learning-based teaching materials through three structured stages: training, mentoring, and reinforcement. During the training phase, teachers were provided with both conceptual and technical understanding of teaching material development using interactive methods that encouraged active participation. The mentoring phase was carried out intensively over the course of one month and focused on content development, evaluation planning, and draft presentations. This phase was tailored to each teacher’s context and subject area. The mentoring sessions resulted in a notable improvement in the quality of the teaching materials, which became more structured, relevant, and aligned with character values and 21st-century competencies. However, participants also encountered various obstacles, such as limited digital literacy, lack of access to appropriate references, and high workload. The reinforcement phase was then designed to restore participants' motivation and address these challenges through reflective sessions, motivational support, and practical digital training. Overall, this program demonstrated that a gradual and collaborative approach can successfully empower teachers to become innovative and reflective learning agents. Moreover, the program fostered a writing culture and helped establish a sustainable professional learning community within the madrasah and pesantren educational environment